Advanced inorganic nanocomposite for decontaminating titanium dental implants. Issue 3 (8th September 2018) - Al‐Hashedi, Ashwaq A.; Laurenti, Marco; Amine Mezour, Mohamed; Basiri, Tayebeh; Touazine, Heithem; Jahazi, Mohamed; Tamimi, Faleh
Abstract: Oral hygiene and regular maintenance are crucial for preserving good peri‐implant health. However, available prophylaxis products and toothpastes, which are optimized for cleaning teeth, tend to contaminate and abrade implant surfaces due to their organic components and silica microparticles, respectively. This study aims to develop an organic‐free implant‐paste based on two‐dimensional nanocrystalline magnesium phosphate gel and hydrated silica nanoparticles (20–30% w/w) for cleaning oral biofilm on titanium dental implants. The surface chemistry, morphology, and bacterial load of contaminated Ti disks before and after decontamination using prophylaxis brushing with toothpaste and implant‐paste were characterized by X‐ray photoelectron spectroscopy (XPS), scanning electron microscopy, and fluorescence spectroscopy. Both commercial toothpastes and implant‐paste remove bacteria, however, only implant‐paste protects Ti metal from abrasion and removes organic contaminants. XPS showed a significant decrease of carbon contamination from 73% ± 2 to 20% ± 2 after mechanical brushing with implant‐paste compared to 41% ± 11 when brushing with commercial toothpastes ( p < 0.05). Fluorescence microscopy revealed that bacteria load on biofilm contaminated Ti (44 × 10 3 ± 27 × 10 3 /µm 2 ) was significantly reduced with the implant‐paste to 2 × 10 3 ± 1 × 10 2 /µm 2 and with a commercial toothpaste to 2.9 × 10 3 ± 7·10 2 /µm 2 . This decay is relatively higher than the removal achieved using rotary prophylaxis brush alone (5 × 10 3 ± 1 × 10 3 /µm 2, p < 0.05). Accordingly, this novel implant‐paste shows a great promise as an efficient decontamination approach. © 2018 Wiley Periodicals, Inc. J. Biomed. Mater. Res. Part B, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 761–772, 2019.